2001
DOI: 10.1038/sj.bjp.0704315
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and its preservative, benzethonium chloride, both inhibit human recombinant α7 and α4β2 neuronal nicotinic acetylcholine receptors in Xenopus oocytes

Abstract: 1 Ketamine is a dissociative anaesthetic that is formulated as Ketalar, which contains the preservative benzethonium chloride (BCl). We have studied the e ects of pure racemic ketamine, the preservative BCl and the Ketalar mixture on human neuronal nicotinic acetylcholine receptors (nAChRs) composed of the a7 subunit or a4 and b2 subunits expressed in Xenopus laevis oocytes. 2 Ketamine inhibited responses to 1 mM acetylcholine (ACh) in both the human a7 and a4b2 nAChRs, with IC 50 values of 20 and 50 mM respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 26 publications
3
71
0
Order By: Relevance
“…Although ketamine has previously been reported to inhibit e.g. NMDA-and nicotinic ACh-receptors and L-type Ca 2þ channels (Coates and Flood, 2001;Hatakeyama et al, 2001;Parsons et al, 1996;Yamakage et al, 1995;Yamakura et al, 1993Yamakura et al, , 2000, these effects are frequently observed at higher concentrations. On the other hand, MXE slightly enhanced the glutamate-evoked increase in [Ca 2þ ] i , but only in the rat cortical culture.…”
Section: Discussionmentioning
confidence: 98%
“…Although ketamine has previously been reported to inhibit e.g. NMDA-and nicotinic ACh-receptors and L-type Ca 2þ channels (Coates and Flood, 2001;Hatakeyama et al, 2001;Parsons et al, 1996;Yamakage et al, 1995;Yamakura et al, 1993Yamakura et al, , 2000, these effects are frequently observed at higher concentrations. On the other hand, MXE slightly enhanced the glutamate-evoked increase in [Ca 2þ ] i , but only in the rat cortical culture.…”
Section: Discussionmentioning
confidence: 98%
“…Studies investigating the sensitivity of numerous ligand-gated channels ectopically expressed in different systems to these compounds came to demonstrate that ␣7 nAChRs as well as ␤4* and ␤2* nAChRs can be inhibited noncompetitively and voltage dependently by ketamine and MK-801 (Ramoa et al, 1990;Buisson and Bertrand, 1998;Furuya et al, 1999). Concentrations of ketamine below 30 M are sufficient to reduce by 50% the activity of ␣7 and ␤4* receptors, whereas Ͼ50 M ketamine is necessary to reduce by 50% the activity of ␤2* nAChRs (Yamakura et al, 2000;Coates and Flood, 2001). Thus, it is conceivable that inhibition of ␣7 and ␤4* nAChRs by ketamine or MK-801 contributes to the dissociative anesthetic properties of these compounds (Tassonyi et al, 2002).…”
Section: Anesthetics and Psychotomimetics Interact With Neuronal Nachmentioning
confidence: 99%
“…Ketamine, in addition to blocking N-methyl-D-aspartate (NMDA) receptors, has been shown to block a7 and a4b2nAChR receptors (Coates and Flood, 2001;Hilmas and Albuquerque, 2002).…”
Section: Introductionmentioning
confidence: 99%